Post‐kidney transplant serum magnesium exhibits a U‐shaped association with subsequent mortality: an observational cohort study. (27th July 2021) - Panthofer, Annalise M.; Lyu, Beini; Astor, Brad C.; Singh, Tripti; Aziz, Fahad; Mandelbrot, Didier; Parajuli, Sandesh; Mohamed, Maha; Djamali, Arjang; Garg, Neetika
Summary: Hypomagnesemia is common in kidney transplant recipients (KTRs). We sought to explore the relationship between Mg and outcomes in KTRs, which may be associated with mortality and thus may be a potential intervention target to improve outcomes. We followed KTRs performed between 01/2000 and 6/2016 at a large US transplant center from 6 months post‐transplant to graft failure, death, or loss to follow‐up. Using Mg as a time‐dependent variable, associations between Mg and outcomes any time after 6 months post‐transplant were evaluated. 3680 KTRs with 50 413 Mg measurements met inclusion criteria. 657 deaths occurred over a median follow‐up of 5.1 years. Compared to Mg of 1.5–1.8 mg/dl, both lower (HR 1.17, 95% confidence interval (CI): 1.07–1.28) and higher (HR 1.16, 95% CI: 1.09–1.23) Mg levels were associated with greater risk of mortality. Similar U‐shaped associations were observed for Mg and cardiovascular disease‐related mortality (HR for Mg ≤1.5 mg/dl: 1.31; CI: 1.03–1.68) and infection‐related mortality (HR for Mg ≤1.5 mg/dl: 1.28; CI: 1.09–1.51), although relationships for Mg >1.8 mg/dl were not statistically significant. Mg exhibits a U‐shaped association with mortality in KTRs, with levels between 1.5 and 1.8 mg/dl associated with the lowest risk. Abstract : Serum magnesium level demonstrated a u‐shaped association with overall mortality in 3, 680 kidney transplant recipients over a mean 5.1‐year follow‐up period. Levels between 1.5 and 1.8 mg/dL were associated with lowest mortality risk.